Analysis of Students Learning Results by Online-Based Learning in Mathematics Subjects With Two Variable Inequality System Material Class X MIPA 1 - Kasmiati; Gusniwati; Andi Aras (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2020)
Corona Virus Disease 2019 (Covid-19) has disrupted conventional learning process. Therefore we need a solution to The challenge. Online learning is one alternative that can overcome the challenge. So this research was conducted to know and analyze students' learning results through online learning in mathematics with the subject of the Two-Variable Inequality System (SPtDV) class X MIPA 1. The method in this study is the descriptive method with a quantitative approach. The instrument used was the test instrument on the SPtDV material with a total of 5 essay questions. The research sample was 14 students of class X MIPA 1 one of the public high schools in Soppeng Regency. The results of this study were four students with high scores, six students with moderate grades, and four students with low scores. Achievement of the lowest percentage of material indicators according to the Level of Ability to Answer the Problems Correctly of Students in a row from high, medium, low, namely solving problems in the area of the settlement set on the SPtDV material. Overall, the achievement of student learning results got a good predicate.